Heart rate variability in the course of chemotherapy and haematopoietic stem cell transplantation for peadiatric patients with haematological malignancies. (29th May 2020) - Kobayashi, Honami; Motoki, Noriko; Yokota, Saori; Kanai, Ayako; Yamazaki, Shoko; Utsumi, Masafumi; Nakazawa, Yozo
Abstract: Background: High-dose chemotherapy and haematopoietic stem cell transplantation are essential for patients with paediatric haematologic diseases, although cardiotoxicity remains a concern. Heart rate variability analysis can evaluate autonomic nervous function interactions with cardiac function. Objective: This study aimed to characterise heart rate variability differences between patients undergoing chemotherapy and controls, and the effects of haematopoietic stem cell transplantation on the autonomic nervous system in patients with haematological malignancies. Methods: Nineteen patients (11 male, median age: 11.6 years) who received conventional chemotherapy followed by transplantation and 19 non-transplant patients (10 male, median age: 11.5 years) receiving chemotherapy only between 2006 and 2018 for haematological malignancies were retrospectively enrolled. Data from 24-hour Holter monitoring were recorded after chemotherapy and before and after transplantation. Heart rate variability was analysed in patients and 32 matched normal controls. Results: There were significant differences between patients and normal controls in all heart rate variability analysis parameters apart from coefficient of variation of RR interval and standard deviation of the average normal RR interval for all 5-minute segments during sleeping. There was a significant difference in the cumulative anthracycline dose and heart rate variability during sleep between the non-transplant and pre-transplant groups. We observed no remarkable differences in time-domain analysis parameters between before and after transplantation, although the low-frequency component of power-spectrum analysis during awake hours was significantly decreased after transplantation. Conclusion: Conventional chemotherapy for paediatric haematologic diseases may be a risk factor for autonomic dysfunction. Further declines in heart rate variability after transplantation appear minor.